AMS Radiocarbon analysis of Greenhouse gases: Method development and application - Melchert, Jan Olaf (2022)
The northern circumpolar permafrost regions are warming faster compared to the global mean. As a result, the duration of annual thaw seasons is increasing, so that the permafrost is subjected to increasingly deep thaw. Within the permafrost zones large amounts of carbon were buried over thousands of years and previously freeze locked due to the cold climate. These carbon sinks are affected by the consequences of global warming and become available for microbial degradation, and thereby potentially turning from carbon sinks into carbon pools. As a result of the microbial degradation of organic matter, the greenhouse gases carbon dioxide and methane are released into the atmosphere, amplifying the global warming, and forcing a positive climate feedback. Among the permafrost deposits, Pleistocene sediments, termed Yedoma, are especially vulnerable to climate change induced rapid thaw and subject to thermoerosion because of their high ice-content. While chemical characterizations of permafrost organic matter and laboratory incubation experiments give information about the degradability of Yedoma organic matter, actual field-studies documenting the extent and exact sources of greenhouse gas release are limited. The analysis of carbon isotopes (13C, 14C) can be used to estimate the age of the permafrost organic matter that is being degraded into greenhouse gases and trace their sources. This is done by collecting carbon dioxide during either field expeditions or during analogue laboratory incubation experiments. Samples are handled in laboratory vacuum rigs, during which the amount of carbon dioxide is quantified and purified from other gases that have been collected along the carbon dioxide. While these methods are overall established and reliable, the analyses are, however, sensitive towards contamination from exogenous carbon sources. The sensitivity towards contamination is amplified towards increasingly smaller sample sizes, down to a few micrograms of carbon. Thus, assessments are necessary to quantify how much ...